PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP RISIKO PERBANKAN - Rachmadan, Adhitya; Harto, Puji (Diponegoro Journal of Accounting, 2013)
This study examined the influence of the corporate governance mechanism to the bank risk. Independent variables in this study are the proportion of independent directors, board size, institutional ownership. state-owned banks, and foreign-owned banks. Banking risk is comprise Capital Risk using Capital Adequacy Ratio (CAR), Credit Risk using Non Performing Loan (NPL) and Liquidity Risk Loan to Deposit Ratio (LDR). Banking companies used in this research are all banking companies listed in Indonesia Stock Exchange (IDX) 2009-2011consisting of 29 banks.so the total observation from the period is 83. The method of analysis used in this study was multiple regression. The empirical results of this study show thatÂ instutional ownership and foreign ownership have a positive effect on CAR and government-ownership have a positive effect on NPL. meanwhile foreign ownership have a positiveÂ effect on LDR